Improving bond of fiber-reinforced polymer bars with concrete through incorporating nanomaterials. (15th June 2022) - Wang, Xinyue; Ding, Siqi; Qiu, Liangsheng; Ashour, Ashraf; Wang, Yanlei; Han, Baoguo; Ou, Jinping
Abstract: The bond between FRP bars and concrete, the foremost performance for implementation of such reinforcements to corrosion-free concrete structures, is still unsatisfied due to the weak nature of duplex film in the interface. The existing approaches show low efficiency in improving the microstructures and bond between FRP bars and concrete. To address these issues, this paper provided a new approach for improving the bond between FRP bars and concrete by incorporating nanomaterials, as well as explored the modifying mechanisms and established the bond-slip models. For these purposes, the pull-out test, scanning electron microscope observation, as well as energy dispersive spectrometry analysis were performed. The experimental results demonstrated that the presence of nanomaterials increased the ultimate bond strengths between glass/carbon FRP bars and concrete by up to 16.2% and 37.8%, while the corresponding slips decreased by 28.7% and 35.4%, respectively. Such modification effects can be attributed to the optimized intrinsic composition and the reduced pore content of hydration products in the interface, especially in the duplex film, through the nanomaterial enrichment and nano-core effects. The bond-slip relationship between FRP bars and concrete with nanomaterials can be accurately predicted by the mBPE model.